New Stable Cell Lines Derived from the Proximal and Distal Intestine of Rainbow Trout (Oncorhynchus mykiss) Retain Several Properties Observed In Vivo - Rolando Pasquariello; Nicole Verdile; Radmila Pavlovic; Sara Panseri; Kristin Schirmer; Tiziana A. L. Brevini; Fulvio Gandolfi (Cells, 2021)
We derived two novel cell lines from rainbow trout (RT) proximal (RTpi-MI) and distal intestine (RTdi-MI) and compared them with the previously established continuous cell line RTgutGC. Intestinal stem cells, differentiating and differentiated epithelial cells, and connective cells were found in all cell lines. The cell lines formed a polarized barrier, which was not permeable to large molecules and absorbed proline and glucose. High seeding density induced their differentiation into more mature phenotypes, as indicated by the downregulation of intestinal stem cell-related genes (i.e., sox9, hopx and lgr5), whereas alkaline phosphatase activity was upregulated. Other enterocyte markers (i.e., sglt1 and pept1), however, were not regulated as expected. In all cell lines, the presence of a mixed population of epithelial and stromal cells was characterized for the first time. The expression by the stromal component of lgr5, a stem cell niche regulatory molecule, may explain why these lines proliferate stably in vitro. Although most parameters were conserved among the three cell lines, some significant differences were observed, suggesting that characteristics typical of each tract are partly conserved in vitro as well.